THE EFFECT OF ORGANIZATIONAL CLIMATE ON TURNOVER INTENTION WITH ORGANIZATIONAL COMMITMENT AS MEDIATING VARIABLE - Ni Made Dwi Puspitawati; Ni Putu Cempaka Dharmadewi Atmaja (Journal of International Conference Proceedings (JICP), 2019)
Human resources as an important factor in the process of achieving company goals are very interested in the quality of each of their employees. A few companies have not realized the importance of human resources. Various problems arise related to human resources, one of them is the high level of employee turnover at Pizza Hut Diponegoro Denpasar, Bali. This is due to pressure to fulfill responsibilities which then reduce their attachment to the company. This indicates a decrease in employee commitment which is characterized by a lack of awareness from within employees to work optimally. This study aims to determine the effect of the organizational climate on organizational commitment and employee turnover intention. The number of samples in this study were 55 employees. This study uses a saturation sampling technique. The method of data collection is questionnaires. Method of data analysis uses path analysis. The results showed (1) organizational climate has a positive and significant effect on organizational commitment, (2) organizational climate has a negative and significant effect on turnover intention, and (3) organizational commitment has a negative and significant effect on turnover intention, (4) organizational commitment mediates influence organizational climate on turnover intention. The research implications show that the more companies pay attention to organizational climate, the employees will feel more attached to the company and reduce the turnover intention.